Enhanced astaxanthin accumulation in Haematococcus pluvialis using high carbon dioxide concentration and light illumination. (May 2018) - Christian, David; Zhang, Jun; Sawdon, Alicia J.; Peng, Ching-An
Graphical abstract: Highlights: Astaxanthin production in H. pluvialis induced by high light intensity and 15% CO2 . Effective astaxanthin induction achieved without using nutrient deficient media. The reported astaxanthin production approach has economical and efficient merits. Abstract: In this study, an economical two-stage method was proposed for the production of natural astaxanthin from Haematococcus pluvialis without a medium replacement step. In stage 1, H. pluvialis were grown under low light illumination until they reached optimal biomass. In stage 2, cells were switched to astaxanthin induction conditions utilizing the combination of high light illumination and elevated carbon dioxide levels (5 or 15%). The introduction of CO2 altered the C/N balance creating a nutrient deficiency without a change of media. The resulting astaxanthin yield was 2–3 times that of using either stressor alone. This astaxanthin induction method has many advantages over current methods including no medium replacement and a short induction time of less than four days.